Reaction pathway and wiring network dependent Li/Na storage of micro-sized conversion anode with mesoporosity and metallic conductivity. Issue 1 (1st December 2014) - Cui, Zhonghui; Li, Chilin; Yu, Pengfei; Yang, Minghui; Guo, Xiangxin; Yin, Congling
Abstract : Highly mesoporous and conductive micro-sized nitride is used as potential conversion LIB and NIB anodes. Superior rate and cycling performances ( e.g. 600 mA h g −1 and 100 mA h g −1 at 2 C for Li- and Na-storage, respectively) benefit from self-reconstruction and preservation of conductive networks. Abstract : Micro-sized or monolithic electrode materials with sufficient mesoporosity and a high intrinsic conductivity are highly desired for high-energy batteries without the trade-off of electrolyte infiltration and accommodation of volume expansion. Here metallic nitrides consisting of mesoporous microparticles were prepared based on a mechanism of solid–solid phase separation and used as conversion anodes for Li and Na storage. Their superior capacity and rate performance during thousands of cycles benefit from the preservation or self-reconstruction of hierarchically conductive wiring networks. The conversion efficiency is also highly dependent on the reaction pathway and product. Exploring more conductive and percolating mass/charge transport networks particularly in a deep sodiation state is a potential solution for activation of Na-driven conversion electrochemistry.